Addition of Aegilops geniculata 1Ug chromosome improves the dough rheological properties by changing the composition and micro-structure of gluten. (1st October 2021) - Guo, Lei; Yu, Liwei; Tong, Jingyang; Zhao, Yiyue; Yang, Yang; Ma, Yanrong; Cui, Lu; Hu, Yingang; Wang, Zhonghua; Gao, Xin
Highlights: The composition and micro-structure of gluten in two wheat lines were analyzed. A novel HMW-GS (NS) was identified in a CS- Ae. geniculata 1Ug disomic addition line. The NS substituted Dx2 subunit with a higher proportion in total HMW-GS. The NS promoted the accumulation of unextractable polymeric protein. The NS was responsible for denser gluten micro-structure and stronger dough strength. Abstract: Aegilops geniculata, a relative of common wheat, has many useful traits for the improvements of wheat varieties. The wheat- Ae. geniculata disomic addition lines (DALs) carrying prior traits need to be characterized for wheat varieties improvement. We currently found that CS-1Ug (Chinese Spring- Ae. geniculata 1Ug DAL) possessed improved dough rheological properties than CS (Chinese Spring) did, and investigated the reasons of those rheological changes in dough. The results showed that CS-1Ug carries a novel high-molecular-weight glutenin subunit (HMW-GS), a substitute for Dx2 from CS, which led to the changes in the relative proportion of individual HMW-GS in total HMW-GSs. Changes in gluten composition improved the stability and elasticity of dough by promoting the accumulation of unextractable polymeric protein, and optimizing the micro-structure of the gluten. The current study provides basic information on CS-1Ug used as a potential resource for future wheat quality breeding.